Theory and applications of formal argumentation : 4th International Workshop, TAFA 2017, Melbourne, VIC, Australia, August 19-20, 2017, Revised selected papers /: 4th International Workshop, TAFA 2017, Melbourne, VIC, Australia, August 19-20, 2017, Revised selected papers. (2018) - Unknown
No abstract available